1991
DOI: 10.1302/0301-620x.73b4.2071645
|View full text |Cite
|
Sign up to set email alerts
|

The cubital tunnel and ulnar neuropathy

Abstract: In type Lb (n = 6) it was tight in positions short of full flexion (90#{176} to 120#{176}). In type II (n = 3) it was replaced by a muscle, the anconeus epitrochlearis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
152
0
14

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(166 citation statements)
references
References 15 publications
0
152
0
14
Order By: Relevance
“…In type II, the CTR is replaced by a muscle, anconeus epitrochlearis. In the previous study, CTR was found in 26 out of 27 elbows examined (96.3%) 4) .…”
Section: Introductionmentioning
confidence: 71%
“…In type II, the CTR is replaced by a muscle, anconeus epitrochlearis. In the previous study, CTR was found in 26 out of 27 elbows examined (96.3%) 4) .…”
Section: Introductionmentioning
confidence: 71%
“…A proposed cause of ulnar nerve dislocation is congenital absence of the cubital tunnel retinaculum [5]. Snapping triceps syndrome was first described in 1970 by Rolfsen.…”
Section: Discussionmentioning
confidence: 99%
“…El retináculo es la banda fibrosa que se extiende desde el epicóndilo hasta la punta del olécranon. Según O'Driscoll y cols., 8 hay cuatro variantes: 0 = ausente con nervio inestable, 1a = retináculo normal, fino sin compresión a la flexión, 1b = retináculo engrosado con aumento de tensión entre 90° y 120° de flexión y 2 = retináculo reemplazado por el músculo anconeus epitrochlearis (Tabla). Dicho músculo está presente en reptiles, anfibios y algunos mamíferos.…”
Section: 5-7unclassified
“…Se ha observado en el 3-28% de las disecciones en especímenes cadavéricos, aunque pocas veces genera síntomas. 6,8 Husarik y cols. 11 han encontrado este músculo accesorio en el 23% de las resonancias magnéti-cas de pacientes asintomáticos.…”
unclassified